MENGKAJI PENGEMBANGAN KURIKULUM TRAVEL AND TOURISM DI SEKOLAH MENENGAH KEJURUAN - Syafruddin Rais (Jurnal Hospitality dan Pariwisata, 2019)
AbstractThe objective of this paper is to examine the development of a travel and tourism curriculum that is relevant to the state of educational institutions and the situation in the industry. In term the suitability of graduate results can be absorbed in the tourism industry. In addition to develop curriculum through the DACUM (Develop a Curriculum) travel and tourism are primarily studied in depth by involving other parties, as well as adjusting the relevance of the relevant institutions. Curriculum development based on DACUM through several stages consists of analysis, design, implementation development and evaluation. As for the preparation of a curriculum developed based on DACUM made on the travel and tourism curriculum consisting of curriculum content structure, learning implementation strategies, learning places, learning assessment and graduate competency results. Where the aim of curriculum development is to produce a relevant travel and tourism curriculum.Keywords: Curriculum, Vocational School, Travel and Tourism. AbstrakArtikel ini bertujuan untuk mengkaji pengembangan kurikulum travel and tourism yang relevan dengan keadaan lembanga pendidikan dan keadaan lapangan yang ada di industri. Agar kesesuaian tenaga hasil lulusan dapat terserap di industri pariwisata. Selain itu untuk pengembangan kurikulum melalui DACUM (Develop A Curriculum) travel and tourism utamanya dikaji secara mendalam dengan melibatkan pihak-pihak lain, serta menyesuaiakan dengan relvansi lembaga terkait. Pengembangan kurikulum berdasarkan DACUM melalui beberapa tahapan terdiri dari analisis, desain, pengembangan implementasi dan evaluasi. Sedangkan untuk penyusunan kurikulum yang dikembangkan berlandaskan DACUM yang dibuat pada kurikulum travel and tourism teridiri dari struktur muatan kurikulum, strategi pelaksanaan pembelajaran, tempat pembelajaran, penilaian pembelajaran dan hasil kompetensi lulusan.  Dimana tujuan pengembangan kurikulum tersebut untuk menghasilkan kurikulum travel and tourism yang relevansi.Kata Kunci: Kurikulum, SMK, travel and tourism.